Inequities in Academic Compensation by Gender: A Follow-up to the National Faculty Survey Cohort Study. (August 2016) - Freund, Karen M.; Raj, Anita; Kaplan, Samantha E.; Terrin, Norma; Breeze, Janis L.; Urech, Tracy H.; Carr, Phyllis L.
Abstract : Purpose: Cross-sectional studies have demonstrated gender differences in salaries within academic medicine. No research has assessed longitudinal compensation patterns. This study sought to assess longitudinal patterns by gender in compensation, and to understand factors associated with these differences in a longitudinal cohort. Method: A 17-year longitudinal follow-up of the National Faculty Survey was conducted with a random sample of faculty from 24 U.S. medical schools. Participants employed full-time at initial and follow-up time periods completed the survey. Annual pretax compensation during academic year 2012–2013 was compared by gender. Covariates assessed included race/ethnicity; years since first academic appointment; retention in academic career; academic rank; departmental affiliation; percent effort distribution across clinical, teaching, administrative, and research duties; marital and parental status; and any leave or part-time status in the years between surveys. Results: In unadjusted analyses, women earned a mean of $20, 520 less than men ( P = .03); women made 90 cents for every dollar earned by their male counterparts. This difference was reduced to $16, 982 ( P = .04) after adjusting for covariates. The mean difference of $15, 159 was no longer significant ( P = .06) when adjusting covariates and for those who had ever taken a leave or worked part-time. Conclusions: The continued gender gap in compensation cannot be accounted for by metrics used to calculate salary. Institutional actions to address these disparities include both initial appointment and annual salary equity reviews, training of senior faculty and administrators to understand implicit bias, and training of women faculty in negotiating skills.